1977
DOI: 10.1128/jb.132.2.511-519.1977
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterization of the two phosphate uptake systems in the fungus Neurospora crassa

Abstract: The kinetics of phosphate uptake by exponentially growing Neurospora crassa were studied to determine the nature of the differences in uptake activity associated with growth at different external phosphate concentrations. Conidia, grown in liquid medium containing either 10 mM or 50 ,AM phosphate, were harvested, and their phosphate uptake ability was measured. Initial experiments, where uptake was examined over a narrow concentration range near that of the growth medium, indicated the presence of a low-affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…200,000 cpm/4mol) into the initial growth medium. Rodlets were prepared from the radioactive conidia in the standard manner, and the 32p present in the final preparation was determined by liquid scintillation spectrometry (7). Radioactive phospholipids were separated by two-dimensional thin-layer chromatography (3).…”
Section: Methodsmentioning
confidence: 99%
“…200,000 cpm/4mol) into the initial growth medium. Rodlets were prepared from the radioactive conidia in the standard manner, and the 32p present in the final preparation was determined by liquid scintillation spectrometry (7). Radioactive phospholipids were separated by two-dimensional thin-layer chromatography (3).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple mechanisms of transport are involved in acquisition of Pi and maintenance of cellular Pi homeostasis. Kinetic analysis has shown that Pi uptake occurs in a bi-phasic manner, and consists of high-affinity (K m 1-10 µM) and low-affinity (K m 100-1000 µM) uptake mechanisms in plants (Clarkson, 1984), bacteria (Rao & Torriani, 1990), yeast (Borst-Pauwels, 1981) and other fungi (Burns & Beever, 1977), including germ tubes of the mycorrhizal fungus, Gigaspora margarita (Thomson et al, 1990).…”
Section: mentioning
confidence: 99%
“…Notwithstanding morphological and membrane changes, differential partitioning of nutrients within hyphae might also contribute to spatial differences in absorption along the hyphal length. Early work by Beever & Burns (1977) indicated that phosphorus absorption by N. crassa mycelia is regulated by the internal inorganic phosphate (PJ concentrations. Subsequent workers have confirmed that a similar regulation of phosphate transport occurs in mycelia of soil-borne basidiomycete saprotrophs (Clipson et al, 1987), AM (Thomson, Clarkson & Brain, 1990) and ECM fungi (Cairney & Smith, 1992).…”
Section: Nutrient Absorptionmentioning
confidence: 99%
“…Swenson, 1960) or rapidlygrowing germlings of filamentous fungi (e.g. Burns & Beever, 1977). It has therefore been suggested that modified conditions favouring efflux of phosphate from the fungus must exist in the apoplast of the fungus-root interface to stimulate rates of efflux sufficiently high to meet the demands of the host (Smith & Smith, 1989.…”
Section: Ectomycorrhizal Symbiosismentioning
confidence: 99%